2007
DOI: 10.1095/biolreprod.107.062505
|View full text |Cite
|
Sign up to set email alerts
|

Annexins Are Candidate Oviductal Receptors for Bovine Sperm Surface Proteins and Thus May Serve to Hold Bovine Sperm in the Oviductal Reservoir1

Abstract: The sperm of eutherian mammals are held in a storage reservoir in the caudal segment of the oviduct by binding to the mucosal epithelium. The reservoir serves to maintain the fertility of sperm during storage and to reduce the incidence of polyspermic fertilization. Bovine sperm bind to the epithelium via seminal vesicle secretory proteins in the bovine seminal plasma protein (BSP) family, namely, PDC109 (BSPA1/A2), BSPA3, and BSP30K, which coat the sperm head. Our objective was to identify the receptors for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
111
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 61 publications
0
111
0
2
Order By: Relevance
“…involved in the establishment and maintenance of the oviductal sperm reservoir in mammals (Suarez 2002;Ekhlasi-Hundrieser et al 2005;Ignotz et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…involved in the establishment and maintenance of the oviductal sperm reservoir in mammals (Suarez 2002;Ekhlasi-Hundrieser et al 2005;Ignotz et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrates mediate the adherence of sperm to the epithelium, with different sugars playing important roles in different species (e.g., Demott et al 1995;Lefebvre et al 1995Lefebvre et al , 1997Ekhlasi-Hundrieser et al 2005). In cows, for example, biochemical studies suggest that fucose residues on oviductal annexins act as receptors for sperm, with several sperm-bound seminal proteins recognizing the fucose moiety (Ignotz et al 2001(Ignotz et al , 2007Gwathmey et al 2006).…”
mentioning
confidence: 99%
“…In addition, Gwathmey et al (2003) have demonstrated that bovine plasma seminal protein PDC-109 promotes bull sperm binding to oviduct epithelium in vitro and that it could be involved in the formation of the oviduct reservoir. Recently, Ignotz et al (2007) found that annexins (that contain fucose residues) might be possible candidates for sperm receptors on bovine oviductal epithelium. Besides, it is known that sulfated glycoconjugates are powerful inducers of sperm release in vitro possibly by promoting sperm capacitation (Gualtieri et al 2005) and/or disrupting the binding of bovine seminal plasma protein to annexins (Ignotz et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ignotz et al (2007) found that annexins (that contain fucose residues) might be possible candidates for sperm receptors on bovine oviductal epithelium. Besides, it is known that sulfated glycoconjugates are powerful inducers of sperm release in vitro possibly by promoting sperm capacitation (Gualtieri et al 2005) and/or disrupting the binding of bovine seminal plasma protein to annexins (Ignotz et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although a considerable amount of knowledge has been gained especially in human and mouse (Almeida et al 1995, Bronson & Fusi 1996, Fusi et al 1996a, 1996b, Nixon et al 2007, Vjugina & Evans 2008, the exact mechanisms of the molecules involved in bovine fertilization are not unequivocally identified at present. Carbohydrates and glycoproteins are assumed to modulate adhesion and binding events during consecutive reproductive processes, like sperm-oviduct adhesion (Lefebvre et al 1997, Suarez et al 1998, Revah et al 2000, Talevi & Gualtieri 2001, Sostaric et al 2005, Ignotz et al 2007, sperm-oocyte interactions (Tulsiani et al 1997, Gougoulidis et al 1999, Amari et al 2001, Tanghe et al 2004a, 2004b, and embryo implantation (Whyte & Allen 1985, Biermann et al 1997.…”
Section: Introductionmentioning
confidence: 99%